Ladies of liberty : the women who shaped our nation - Roberts, Cokie (William Morrow, 2008)
Cokie Roberts sheds new light on the generation of heroines, reformers, and visionaries who helped shape our nation with this blend of biographical portraits and behind-the-scenes vignettes chronicling women's public roles and private responsibilities. Drawing on personal correspondence, private journals, and other primary sources--many of them previously unpublished--Roberts brings to life the extraordinary accomplishments of women who laid the groundwork for a better society. Almost every quotation here is written by a woman, to a woman, or about a woman. From first ladies to freethinkers, educators to explorers, this exceptional group includes Abigail Adams, Margaret Bayard Smith, Martha Jefferson, Dolley Madison, Elizabeth Monroe, Louisa Catherine Adams, Eliza Hamilton, Theodosia Burr, Rebecca Gratz, Louisa Livingston, Rosalie Calvert, Sacajawea, and others.--From publisher description.